Operationalizing spatial justice: a transdisciplinary framework for territorial equity in Portugal - Gonçalves, Jorge; Jorge, Sílvia; Nunes da Silva, Fernando; Amorim, Julianno; Vale de Paula, Paula; Marques, Robert; Cepni, Hilal (Frontiers in Built Environment, 2025)
This paper presents the Território.justo.pt project as an innovative initiative to operationalise the concept of spatial justice within the Portuguese territorial context. Drawing on foundational works by Lefebvre, Harvey, Soja, and Fainstein, the project develops a transdisciplinary and data-driven framework to identify and address territorial disparities across Portuguese municipalities. Through the combination of participatory workshops and cluster analysis (SPSS), the study maps spatial injustice along three core dimensions: mobility, economy, and governance. Four municipalities were also selected as representative case studies of each cluster, laying the groundwork for future research. These municipalities offer an opportunity to further investigate spatial (in)justice in context-specific ways and to test the operational applicability of the proposed framework.